Polymethoxylated flavonoids in citrus fruits: absorption, metabolism, and anticancer mechanisms against breast cancer - Wang, Yiyu; Mou, Yuan; Lu, Senlin; Xia, Yuhua; Cheng, Bo (PeerJ, 2024)
Polymethoxylated flavonoids (PMFs) are a subclass of flavonoids found in citrus fruits that have shown multifunctional biological activities and potential anticancer effects against breast cancer. We studied the absorption, metabolism, species source, toxicity, anti-cancer mechanisms, and molecular targets of PMFs to better utilize their anticancer activity against breast cancer. We discuss the absorption and metabolism of PMFs in the body, including the methylation, demethylation, and hydroxylation processes. The anticancer mechanisms of PMFs against breast cancer were also reviewed, including the estrogen activity, cytochrome P-450 enzyme system, and arylhydrocarbon receptor (AhR) inhibition, along with various molecular targets and potential anticancer effects. Although PMFs may be advantageous in the prevention and treatment for breast cancer, there is a lack of clinical evidence and data to support their efficacy. Despite their promise, there is still a long way to go before PMFs can be applied clinically.
Keywords: Polymethoxylated flavonoids; Absorption and metabolism; Molecular mechanism; Anti-breast cancer